Virome of Rhipicephalus ticks by metagenomic analysis in Guangdong, southern China - Guo, Luanying; Ma, Jun; Lin, Junwei; Chen, Meiyi; Liu, Wei; Zha, Jin; Jin, Qinqin; Hong, Hongrong; Huang, Weinan; Zhang, Li; Zhang, Ketong; Wei, Zhengkai; et al. (Frontiers in Microbiology, 2022)
Tick-borne viruses (TBVs) have increasingly caused a global public health concern. In this study, Rhipicephalus ticks were collected in Guangdong, southern China for identification of RNA viruses. Meta-transcriptome analysis revealed a high viral diversity in Rhipicephalus ticks, resulting in discovery of 10 viruses, including Lihan tick virus, Brown dog tick phlebovirus 1 and 2 in the family Phenuiviridae, Mivirus and Wuhan tick virus 2 in the family Chuviridae, Wuhan tick virus 1 in the family Rhabdoviridae, Hepacivirus in the family Flaviviridae, Guangdong tick quaranjavirus (GTQV) in the family Orthomyxoviridae, Guangdong tick orbivirus (GTOV) in the family Reoviridae, and Guangdong tick Manly virus (GTMV) of an unclassified family. Phylogenetic analysis showed that most of these TBVs were genetically related to the strains in other countries than in China, and GTQV, GTOV and GTMV may represent novel viral species. These findings provided the evidence of long-distance spread of these TBVs in Guangdong, southern China, suggesting the necessity and importance of TBV surveillance.